The Orphan Nuclear Receptor 4A1: A Potential New Therapeutic Target for Metabolic Diseases - Lei Zhang; Qun Wang; Wen Liu; Fangyan Liu; Ailing Ji; Yanzhang Li (Journal of Diabetes Research)
Orphan nuclear receptor 4A1 (NR4A1) is a transcriptional factor of the nuclear orphan receptor (NR4A) superfamily that has sparked interest across different research fields in recent years. Several studies have demonstrated that ligand-independent NR4A1 is an immediate-early response gene and the protein product is rapidly induced by a variety of stimuli. Hyperfunction or dysfunction of NR4A1 is implicated in various metabolic processes, including carbohydrate metabolism, lipid metabolism, and energy balance, in major metabolic tissues, such as liver, skeletal muscle, pancreatic tissues, and adipose tissues. No endogenous ligands for NR4A1 have been identified, but numerous compounds that bind and activate or inactivate nuclear NR4A1 or induce cytoplasmic localization of NR4A1 have been identified. This review summarizes recent advances in our understanding of the molecular biology and physiological functions of NR4A1. And we focus on the physiological functions of NR4A1 receptor to the development of the metabolic diseases, with a special focus on the impact on carbohydrate and lipid metabolism in skeletal muscle, liver, adipose tissue, and islet.